Event-triggered coordination of multi-agent systems via a Lyapunov-based approach for leaderless consensus - Chen, Ci (2022)
In this work, an event-triggered coordination problem for multi-agent systems with general linear dynamics is considered over directed communication graphs with a spanning tree. We study such a problem by using a Lyapunov equation for leaderless consensus. It is shown that a Lyapunov-based approach can complete stability analysis of event-triggered consensus of multi-agent systems over general directed graphs.